Social Change in the Bajo Community in Binanga Sombaiya Village, Selayar Islands Regency, Indonesia - Sofyan Kaepa; Tasrifin Tahara; Wahyu Chandra (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
This study aims to discover the social changes in the Bajo fishing community in Bajo Hamlet, Binanga Sombaiya Village, as well as the factors that cause these changes. This research uses a descriptive qualitative approach, conducted on June 12 – June 19, 2024, in Bajo Hamlet, Binanga Sombaiya Village, Bontosikuyu District, Selayar Islands Regency, South Sulawesi, Indonesia. The informants from this study are the community, community leaders, the younger generation, and village government officials, with 10 informants. The study results show several social changes in Binanga Sombaiya Village, such as changes in the way of going to sea and the use of fishing gear, changes related to identity and self-perspective, and changes in lifestyle and settlement patterns. Several factors that triggered these changes were modernization, changing religious beliefs, climate change, and the intensity of interaction with other tribes.